2020
DOI: 10.5194/isprs-archives-xliii-b3-2020-1199-2020
|View full text |Cite
|
Sign up to set email alerts
|

Volume Estimation of Fuel Load for Hazard Reduction Burning: First Results to a Voxel Approach

Abstract: Abstract. In 2019/20 over 100 severe bushfires burned across the continent of Australia. The severity of these fires was exacerbated by many factors, including macroclimatic effects of global warming and, at the meso and micro scales, land management practices. The bushfire phenomenon cannot be stopped, however better management practices can help counter the increasing severity of fires. Hazard reduction burning is a method where certain vegetation is deliberately burned under controlled circumstances to thin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…They lacked information related to the presence of different vegetation parts, such as foliage, branches, trunks, or bark, which are relevant for wildfire considerations. In this context, some studies have attempted to categorize voxels according to their class to enhance fuel quantification (e.g., [59,60]). However, this can be a complex task in forest environments of very high structural heterogeneity, where different fuel classes are intermingled.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They lacked information related to the presence of different vegetation parts, such as foliage, branches, trunks, or bark, which are relevant for wildfire considerations. In this context, some studies have attempted to categorize voxels according to their class to enhance fuel quantification (e.g., [59,60]). However, this can be a complex task in forest environments of very high structural heterogeneity, where different fuel classes are intermingled.…”
Section: Discussionmentioning
confidence: 99%
“…Estimation of the fuel load was performed by calculating the volume of the normalized point clouds. For this purpose, a voxelization process was conducted, which has been reported as a well-suited approach for estimating forest fuels (e.g., [59][60][61][62]) and allows for simplifying the huge amount of data coming from ground-based LiDAR systems [63][64][65][66][67]. In doing so, the effect of uneven point distributions, many of which tend to be located closer to the sensor, is normalized [64,65].…”
Section: Voxelization and Fuel Load Quantificationmentioning
confidence: 99%
“…Similar conditions are emerging in Asia and the Americas as extended drier and hotter summer seasons produce increased volumes of dry understory fuels [23,24]. Most recent studies have concluded that this trend will continue [14,25].…”
Section: Introductionmentioning
confidence: 81%
“…The influence of voxel size on the precision of canopy heigh was noted and a voxel size of 18 m was identified as the most fitting voxel size for this work. While Eusuf et al (2020) presented an automated method for measuring fuel load in a multi-layered forest in Newcastle, Australia. In this work a voxel size of 0.4 m was selected for the representation of the fuel load and classification of the near-surface fuel.…”
Section: Literature Reviewmentioning
confidence: 99%